Association of microalbuminuria with severity of coronary artery disease in diabetic patients: a cross-sectional study - Vara, Ranjith; Khan, M. Adnan Ali; Krishnamurthy, Shreya; Konidena, SriSahithi (International Journal of Advances in Medicine, 2025)
Background: Microalbuminuria is recognized as a significant indicator of early cardiovascular problems and diabetic renal impairment. It is indicative of vascular and endothelial damage and could be predictive of coronary atherosclerosis. The purpose of this investigation is to stratify coronary angiographic features in individuals having type 2 diabetes mellitus (T2DM), microalbuminuria and suspected of suffering from ischemic heart disease. Methods: The cross-sectional prospective study had been performed over two years. Individuals who had T2DM undergoing coronary angiography for suspected ischemic heart disease but no prior history of myocardial infarction were chosen for the investigation. Results: The investigation involved coronary angiography for 77 individuals with T2DM suspected of suffering from ischemic heart disease. 61 (79%) of the 77 individuals had normoalbuminuria, and 16 (21%) had microalbuminuria. Six individuals with normal coronary arteries were in normoalbuminuria group, while none in the microalbuminuria group had normal coronary arteries, as determined by angiography. All diabetic patients exhibiting microalbuminuria had multiple coronary artery diseases (CAD), which is indicative of a severe condition. Conclusions: Microalbuminuria has been demonstrated to predict a more severe form of CAD along with intricate and widespread coronary lesions in people suffering from T2DM. Chronic smokers and elderly people having T2DM are more affected. Microalbuminuria has been associated with a severe form of coronary disease in these individuals. It was discovered that individuals with microalbuminuria were prone to more severe diffuse illness, and many had smaller caliber arteries that would be difficult to revascularize.